Multicomponent, Solvent-Free Synthesis of 1-Amidoalkyl-2-naphthols in the Presence of H3+xPMo12-x Vx O40 Heteropolyacids as Recyclable and Green Catalysts - Fatemeh F. Bamoharram; Majid M. Heravi; Mina Roshani; Mohammad J. Sane Charkhi (E-Journal of Chemistry)
A rapid and efficient one-pot method for the synthesis of 1-amidoalkyl-2-naphthols has been developed in the presence of mixed-addenda vanadium(V)-substituted polyoxomolybdates including: H3+xPMo12-xVxO40 (x=1-3) heteropolyacids (HPAs) as recyclable catalysts under solvent-free conditions. In all cases heteropolyacid with x = 3 gave the highest yield under solvent-free conditions.